Differential predation pressure on island pit vipers shape their niches and defensive behavior - Banci, Karina R.S. [UNESP]; Siqueira, Lucas H.C. [UNESP]; Torello-Viera, Natália F.; Marques, Otavio A.V. [UNESP] (Brill Academic Publishers, 2024)
Animals are naturally exposed to several predators, and, given that a single encounter with a predator may cause prey’s death, natural selection will strongly act upon its defensiveness. Therefore, defensive behavior is strongly shaped by predation pressure. Predation rate in islands tends to be relaxed due to lower abundance of predators. The aim of this study was to test the hypothesis that predation rates upon the two island pit vipers Bothrops alcatraz and B. insularis would be lower than correlated mainland B. jararaca. Additionally, we evaluated the defensive behavior of these island snakes in the field to compare with the mainland B. jararaca. Predation pressure upon the insular species was assessed utilizing plasticine replicas, and we evaluated their defensive behavior to approach. These data were compared to those previously reported for B. jararaca. We found a lower predation pressure on B. insularis (from the smaller area) than on B. alcatraz and B. jararaca from the urban mainland forest fragment (areas with intermediate size), and all of them showed lower predation pressure than B. jararaca from the continuous mainland forested area. In the field, island snakes show narrower defensive repertoire than B. jararaca, since most B. insularis fled, and B. alcatraz either fled or remained immobile on approach. Apparently, the predation pressure to which these island pit vipers are exposed shapes their defensive behavior, as well as the niches exploited by them.
Keywords: Bothrops Alcatraz; Bothrops insularis; Bothrops jararaca; defense; plasticine replicas